Effect of melatonin and vitamin E on diabetes-induced learning and memory impairment in rats - Tuzcu, Mehmet; Baydas, Giyasettin (Elsevier Science Bv, 2006)
Previous studies indicate that diabetes mellitus might be accompanied by a certain erosion of brain function such as cognitive impairment. The aim of this study was to examine and compare the effects of melatonin and vitamin E on cognitive functions in diabetic rats. Diabetes was induced in male albino rats via intraperitoneal streptozotocin injection. Learning and memory behaviors were investigated using a spatial version of the Morris water maze test. The levels of lipid peroxidation and glutathione were detected in hippocampus and frontal cortex. The diabetic rats developed significant impairment in learning and memory behaviors as indicated by the deficits in water maze tests as compared to control rats. Furthermore, lipid peroxidation levels increased and glutathione concentration decreased in diabetic rats. Treatment with melatonin and vitamin E significantly ameliorated learning and memory performance. Furthermore, both antioxidants reversed lipid peroxidation and glutathione levels toward their control values. These results suggest that oxidative stress may contribute to learning and memory deficits in diabetes and further suggest that antioxidant melatonin and vitamin E can improve cognitive impairment in streptozotocin-induced diabetes. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: melatonin; vitamin E; diabetes; learning; memory